Investigation of nutritional status using the Mini Nutritional Assessment‐Short Form and analysis of the relevant factors in patients with head and neck tumour. (20th December 2016) - Yanagi, Ayaka; Murase, Mai; Sumita, Yuka I.; Taniguchi, Hisashi
Abstract : Objective: The aims of this study were to reveal the nutritional status of patients after head and neck tumour treatment by using the Mini Nutritional Assessment‐Short Form (MNA‐SF) and to analyse the factors affecting nutritional status in patients with head and neck tumour. Background: Elderly patients with loss of teeth and maxillary/mandibular bone due to head and neck tumour treatment could be at high risk of malnutrition. However, there are few reports on the nutritional status of these patients. Materials and methods: Forty‐six participants (average age 74.7 years) were selected from patients who visited the maxillofacial prosthetics clinic of Tokyo Medical and Dental University Hospital Faculty of Dentistry in Japan. Nutritional status was evaluated using the MNA‐SF. Multiple regression analysis was used to identify predictors affecting MNA‐SF score. The candidate explanatory variables were age, sex, maxillofacial prosthesis use, number of residual teeth, resection side, neck dissection and treatment option. Results: The results showed that approximately half of the patients were at risk of malnutrition, and a regression equation for MNA‐SF score was developed using two predictors: maxillofacial prosthesis use and neck dissection. Conclusion: Use of a maxillofacial prosthesis can improve nutritional status. On the other hand, a medical history of neck dissection can decrease nutritional status.